Professional ethics of the university teacher of psychology concerning a multiparadigmatic panorama - Montgomery Urday, William (2020)
This study aims to remind that psychology is a multi-paradigmatic science, which is why teaching psychology in higher education is eclectic in nature in order to reflect on the alternatives available in this respect. However, when it comes to practical performance, the personal theoretical orientation of each professor may lead him or her to opt for and present in an unethical manner topics that are not consistent with the desired outcomes of introducing students with the array of conceptualization options and their specific applications. This bias can occur when professors favor an alternative at the expense of others or make a biased comparison between them, forbid or penalize answers that they consider invalid, or neglect and avoid clarifying topics covered in class. This study highlights that the transmission of updated knowledge on a specific topic or domain is key for adequate faculty performance, which should rise above personal or professional preferences.